Intramuscular hematoma of the vastus lateralis following percutaneous skeletal muscle microbiopsy: a case report. Issue 19 (11th October 2021) - Drouin, Patrick J.; Islam, Hashim; Simpson, Craig A.; Gurd, Brendon J.
Abstract: Recently, percutaneous microbiopsy needles have been used as a less invasive alternative to the Bergstrom needle for obtaining human skeletal muscle biopsy to assess changes in protein content, gene expression, and enzymatic activities. Unlike the Bergstrom muscle biopsy procedure, potential complications associated with microbiopsies of human skeletal muscle have not been documented. Therefore, the present case report follows a young male's recovery from a muscle biopsy‐induced hemorrhage/hematoma of the right vastus lateralis with the specific aims of (1) informing future participants, researchers, and clinicians on expected time course of recovery and (2) informing methods to minimize future participant adverse event risk during and after the percutaneous microbiopsy procedure. The present case report demonstrates that the inadvertent hemorrhaging of a neighboring vessel by percutaneous microbiopsy procedure can be debilitating. To minimize the risk of muscle biopsy‐induced hemorrhage/hematoma, we advise post‐biopsy compression for up to 15 min and post‐biopsy follow‐up should be completed for up to 72 h. When there is indication of hematoma development, compression should be applied, and the participant should avoid exercise and physical activity. Abstract : The present case report demonstrates that the inadvertent hemorrhaging of a neighboring vessel by percutaneous microbiopsy procedure can be debilitating. To minimize the risk of muscle biopsy‐induced hemorrhage/hematoma, post biopsy compression is recommended for up to 15 min and post biopsy follow‐up should be completed for up to 72 h.